Análisis sobre el principio de inocencia en los procesos de infracciones de violencia contra la mujer en la Unidad Judicial Penal de Cayambe entre el periodo enero a marzo de 2021. - Mora, Kennyshka A. (2022)
The general objective of this scientific article is: To analyze the principle of innocence in the processes of infractions of violence against women in the Criminal Judicial Unit of Cayambe between the period January to March 2021. The Constitution of the Republic of Ecuador, recognizes within the list of protection rights, the basic guarantees of due process, in which the presumption of innocence is incorporated. This case study will address the guarantee of the presumption of innocence within the scope of due process. We will analyze a practical case of violation of violence against women to discuss our topic. The way in which justice operators conceive and apply this guarantee within the specific cases in which they must deliver justice will be analyzed. It must be borne in mind that judges, especially criminal judges, within the neo-constitutional paradigm with which the current constitution was designed, make judges guardians of constitutional rights and guarantees. Therefore, it is important to understand the importance of extending this concept to adopt social policies and legislation in the face of the concrete reality, in attention to the ways in which men and women are distinguished in terms of access to employment opportunities, health or education, which which is critical for true social transformation. It is also clear that there is not enough understanding in relation to the normative and dogmatic contents, since the application of precautionary measures to all those reported for domestic violence, especially the arrest of the accused, can generate a distortion of the spirit of the laws, and violate the principle of innocence, which must continue to be an essential part of criminal proceedings.